(untitled) (Journal of the College of Basic Education, 2022)
The research aim is to know the effect of the use of Buxton Model in acquisition of mathematical concepts for second class students of intermediate School . In order to achieve the objective of the research , one hypothesis was set up (there was no statistical indication difference at (0.05) level between medium marks of the experimental group of students who were studying Mathematics according to Buxtons Model and medium marks of control group of students who were studying Mathematics in the ordinary method in the test of acquisition of mathematical concepts ).The two researchers had chosen two groups : experimental group of (30) students and control group of (32) students ; The experimental group studied according to Buxton model and the control group studied according to the ordinary method Equivalence for the two groups in time age and previous achievement was done ; the subject was restricted to chapter five (open sentences ) and chapter eight (triple space engineering ) of Mathematics Book for second intermediate class . (99) behavioral objectives were for mulated according to bloom classification of levels (remembering , comprehension ,application ). (28) teaching plans were prepared : (14) plans for each group . The two researchers prepared the instrument of the research : Test of acquisition of Mathematical concepts . After that , six mathematical concepts were defined in open sentences and triple space chapters : (18) items for each (3) paragraphs to measure levels of (remembering ,excellence ,application ). Psychometric characteristics were verified by applying it on asample (not the sample of research ). Constancy was calculated by re-test of the sample (not the sample of research) after one week of first application using Pearsons coefficient of connection (0.85) The two researchers used a number of statistical means according to research requirements and nature . Then , that persons of both groups were subjected to test . The results had shown the excellence of the experimental group that studied according to Buxton Model with three acquired concepts against the control group The two researchers recommended to concentrate on the use of Buxton Model in teaching for its importance in the acquisition of mathematical concepts for different academic stages . The two researchers also suggested to conduct several similar studies .